Effect of Tannase on Chemical Parameters of Cashew Apple Juice (Anacardium occidentale Linn) - Yunita Arian Sari Anwar (ALCHEMY Jurnal Penelitian Kimia, 2015)
We previously produced tannase from Aspergillus niger using solid state medium. In the present study the enzyme used cashew apple juice. The aim this research was to know effect of tannase on chemical parameters of cashew apple juice. The concentration of tannase used was 0%; 0.02%; 0.04%; 0.06%; 0.08% and 0.1% (v/v). The chemical properties of the juice produced by enzymatic method were compared with the juiced produced through high temperature treatment (100oC).  This research showed that the addition of 0.1% of tannase enzyme provide the best product according to the lower content of tannins than the content of tannins in the juice produced with high temperature treatment. The tannase treatment did not change the vitamin C content, content of protein and pH. Meanwhile, high temperature treatment decreased the content of vitamin C and protein.